Kajian Teknis Unjuk Kerja Peralatan Mekanis Terhadap Nilai Standar Unjuk Kerja Peralatan berdasarkan Kepmen No. 1827 Tahun 2018 pada Kegiatan Penambangan Batu Andesit di PT Mitra Multi Sejahtera, Kecamatan Cikalong Kulon, Kabupaten Cianjur - Dicky William; Zaenal; Sriyanti (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Based on data from the Ministry of Energy and Mineral Resources, regarding the technical achievement target of equipment performance, especially in the West Java area, the level of tool performance achievement is less than the value set in ESDM Ministerial Decree No. 1827 of 2018. So it is necessary to conduct a study related to factors that can affect achievement of the performance value of the equipment. A performance activity can be achieved by reviewing ongoing mining activities in the next 1 month which includes activities and transportation. One of the efforts is to know the productive time, calculate the time that occurs and the time to repair the tool if it breaks. The results of a technical study on the achievement of the performance value of mechanical devices referring to the Minister of Energy and Mineral Resources Decree No. 1827 of 2018 show the achievement of the performance value of the tool except for the Use of Availability (UA) parameter for loading and unloading equipment which has a value of 61.70% (not achieved). The results of the assessment of the productivity of mechanical equipment showed achievement with a value for equipment of 83.14% (not achieved) and for transportation equipment of 83.80% (not achieved). To increase yields on parameters that are not achieved, it is necessary to carry out handling in the form of maximizing stone stock at the loading point so as not to cause long waiting times for mechanical equipment and also maintenance and repair of haul roads so that conveyance time can be trimmed so that the equipment does not require a long waiting time. time and maximize productivity value. The performance value of the Kobelco SK-200 Excavator backhoe loading tool includes Mechanical Availability (MA) of 98.95% (achieved), Physical Availability (PA) of 99.35% (achieved), Use of Availability (UA) of 61.70 % (not achieved) and Effective Utilization (EU) of 61.30% (not achieved). While the overall performance value of the DT Nissan Diesel CW450B conveyance unit consists of Mechanical Availability (MA) which is 99.68 – 99.88% (achieved), Physical Availability (PA) is 99.75 – 99.90% (achieved), Use of Availability (UA) is 77.94 – 79.89% (achieved) and Effective Usage (EU) is 77.85 – 79.71% (achieved). Abstrak. Berdasarkan data statistik Kementerian ESDM, mengenai target ketercapaian unjuk kerja peralatan mekanis di perusahaan tambang, khususnya di daerah Jawa Barat memiliki tingkat nilai ketercapaian unjuk kerja alat kurang dari nilai yang sudah ditetapkan pada Kepmen ESDM No.1827 Tahun 2018. Sehingga perlu dilakukaknnya kajian teknis yang berhubungan dengan faktor yang dapat mempengaruhi ketercapaian nilai unjuk kerja peralatan mekanis tersebut. Suatu nilai unjuk kerja peralatan mekanis dapat dicapai dengan mengkaji kegiatan penambangan yang sedang berlangsung pada 1 (satu) front penambangan yang mencakup aktivitas muat dan angkut. Salah satu upayanya ialah dengan mengetahui waktu produktif, menghitung waktu hambatan dan waktu perbaikan alat jika terjadi kerusakan. Hasil kajian teknis ketercapaian nilai unjuk kerja alat mekanis yang mengacu pada pada Kepmen ESDM No.1827 Tahun 2018 menunjukkan ketercapaian nilai unjuk kerja alat kecuali pada parameter Use of Availability (UA) alat muat yang memiliki nilai 61,70 % (tidak tercapai). Sedangkan hasil kajian pencapaian produktivitas alat mekanis menunjukkan ketercapaian dengan nilai untuk alat muat sebesar 83,14 % (tidak tercapai) dan alat angkut sebesar 83,80% (tidak tercapai). Untuk meningkatkan hasil pada parameter yang tidak tercapai, perlu dilakukan penanganan berupa memaksimalkan stok batu pada loading point agar tidak menimbulkan waktu tunggu alat mekanis yang lama dan juga perawatan dan perbaikan jalan angkut agar waktu angkut alat angkut dapat dipangkas sehingga alat muat tidak mengalami waktu tunggu yang lama dan memaksimalkan nilai produktivitas. Nilai unjuk kerja alat muat Excavator backhoe Kobelco SK-200 mencakup Mechanical Availability (MA) sebesar 98,95% (tercapai), Physical Availability (PA) sebesar 99,35% (tercapai), Use of Availability (UA) sebesar 61,70% (tidak tercapai) dan Effective Utilization (EU) sebesar 61,30% (tidak tercapai). Sedangkan nilai unjuk kerja keseluruhuan unit alat angkut DT Nissan Diesel CW450B mencakup Mechanical Availability (MA) ialah 99,68 – 99,88% (tercapai), Physical Availability (PA) ialah 99,75 – 99,9% (tercapai), Use of Availability (UA) ialah 77,94 – 79,89% (tercapai) dan Effective Utilization (EU) ialah 77,85 – 79,71% (tercapai).